Able seacat Simon - Barrett-Lee, Lynne (Simon & Schuster, 2016)
Simon is discovered in the Hong Kong docks in 1948 and smuggled on board the H.M.S Amethyst by a British sailor who takes pity on the malnourished kitten. The young cat quickly acclimates to his new water-borne home, establishing himself as the chief rat-catcher in residence while also winning the hearts of the entire crew. Then the Amethyst is ordered to sail up the Yangtze to take over the guarding of the British Embassy, and tragedy strikes as the ship comes under fire from Communist guns. Many of the crew are killed and Simon is among those who are seriously wounded. Luckily, with the help of the ship's doctor, the brave cat makes a full recovery and is soon spending time with the injured men in the sick bay, purring and keeping their spirits up. News of Simon's heroism spreads and he becomes famous world-wide but it is still a long journey back to England for both the crew and the plucky little cat known as 'Able Seacat Simon'.
Keywords: Simon, : kissa (fiktiivinen hahmo); 1940-luku; laivasto; lemmikkieläimet; sankarit; kissa; sisällissota; Kiina; Jangtse; Iso-Britannia